Organic Geometry : An exploration of form in contemporary Irish Craft - Mulrooney, Ann (Kilkenny : National Craft Gallery)
Byrne, Edmond ; Carrigy, Tara ; Dunne, Terry ; Elliot, Anita ; Faustino, Gina ; Flynn, Liam ; Flynn, Sara ; Geraghty, Cliona ; Hanvey, Mark ; Hartung, Stevan ; Kay, Alison ; Landweer, Sonja ; Lee, John ; Ludick, Andrew ; Mc Cormick, Kathleen ; Mc Rory, Deirdre ; Neeson, Mary ; Nolan, Ann ; O'Donovan, Nuala ; Paul, Debbie ; Phillips, Jill ; Ray, Michael ; Reed, Inga ; Rogers, Deirdre ; Scarff, Leo ; Scott-Mc Carthy, Paget ; Scroope, Peter ; Sheen, Rowena ; Singleton, Eileen ; Walsh, Joseph
Gift Flanders DC
boek